2014
DOI: 10.1186/1297-9716-45-49
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid changes in the spike protein of feline coronavirus correlate with systemic spread of virus from the intestine and not with feline infectious peritonitis

Abstract: Recent evidence suggests that a mutation in the spike protein gene of feline coronavirus (FCoV), which results in an amino acid change from methionine to leucine at position 1058, may be associated with feline infectious peritonitis (FIP). Tissue and faecal samples collected post mortem from cats diagnosed with or without FIP were subjected to RNA extraction and quantitative reverse-transcriptase polymerase chain reaction (qRT-PCR) to detect FCoV RNA. In cats with FIP, 95% of tissue, and 81% of faecal samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
144
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(150 citation statements)
references
References 30 publications
4
144
1
1
Order By: Relevance
“…One additional cat not affected by FIP (IHC negative on all organs) tested positive on nRT-PCR for FCoV. Indeed, viral systemic spread is not uncommon in FCoV-infected cats not affected by FIP (Porter et al, 2014;Barker et al, 2017).…”
Section: Caseloadmentioning
confidence: 97%
“…One additional cat not affected by FIP (IHC negative on all organs) tested positive on nRT-PCR for FCoV. Indeed, viral systemic spread is not uncommon in FCoV-infected cats not affected by FIP (Porter et al, 2014;Barker et al, 2017).…”
Section: Caseloadmentioning
confidence: 97%
“…These would seem to be logical mutations to incorporate into a RT-qPCR. However, a more recent study by Porter et al (2014) demonstrated the presence of coronavirus with the FIPV-specific fusion peptide mutation in tissues of healthy cats. They concluded that the spike fusion region specific mutation was an adaptation of FECV for growth in blood monocyte/ macrophages and not directly related to disease.…”
Section: Introductionmentioning
confidence: 99%
“…The feline coronavirus (FCoV) possesses a large genome (almost 30 kb) organized in 11 putative open reading frames (ORFs) encoding 16 nonstructural proteins involved in virus replication as well as four structural proteins (Spike, S; Membrane, M; Nucleocapsid, N; Envelope, E) and five accessory proteins (3 a-c, 7a and b) (Kipar and Meli, 2014). Not yet well characterized viral mutations, along with an inadequate immune response of the host, lead to the inevitably deadly disease of felids called feline infectious peritonitis (FIP) (Pedersen, 2009;Porter et al, 2014). The diagnosis of FIP is challenging in vivo and must rely on several clinico-pathological tests (e.g.…”
Section: Introductionmentioning
confidence: 99%